Estudio comparativo de las de los perfiles semanales de creatin kinasa, urea y variabilidad de la FC en remeros de élite españoles - Cachadina, E. S.; la Cruz Torres, B.; Naranjo Orellana, J. (Archivos de medicina del deporte, 2012)
It is known that exercise fatigue can be detected through biochemical markers as Creatine Kinase (CK) and Urea; but recently, several studies have demonstrated that the Autonomic Nervous System (ANS) behaviour could be also an important indicator of overtraining and fatigue. Heart Rate Variability (HRV) analysis, has currently bec ome the main tool for the assessment of ANS implication in overtraining syndrome, fatigue and training load quantification. In order to compare both methods, the aim of the study was to examine the relationship between HRV parameters and CK and Urea profiles (CK/U-P). The study comprised 11 Under 23 male rowers of the Spanish National Team, which underwent during 5 consecutive days in competitive season, an analysis of CK/U-P and sleeping HRV during the night. The present research did not find significant correlations between CK/U-P and HRV parameters; but did find correlations among HRV parameters. The study also showed a clear qualitative association between CK profile and HRV parameters. Urea profile was steady during the whole study but HRV parameters and CK profile oscillated. The correlations among HRV parameters suggest that for future studies the calculation of all HRV domains could not be necessary. The qualitative correlation between HRV parameters and CK profile might indicate that higher training loads may be related to higher parasympathetic activity if the athletes recover after the training.